Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Bank SULSELBAR Kantor Pusat Makassar - Pra Gemini (Jurnal Online Manajemen ELPEI, 2021)
The aims of this study are: 1) To determine the effect of leadership style on employee performance. 2) To determine the effect of work motivation on employee performance. 3) To find out which is the most influential between leadership style and work motivation on employee performance. To answer these problems, the authors used a quantitative and qualitative approach using primary data in the form of a questionnaire which was distributed to the research population which was reduced in population by using the slovin formula with an error rate of 0.05%. The data analysis technique used in this study is a multiple linear regression analysis technique. Based on the results of research conducted at PT. Bank Sulselbar Makassar Head Office. The results of the t test analysis show that the variable Leadership Style (X1) has a significant effect on employee performance (Y). The results of the t test analysis show that the motivation variable (X2) has no significant effect on employee performance (Y). The most dominant variable that influences employee performance is the leadership style variable (X1).